Capturing the heterogeneity of life on the streets: A person-centered analysis of street histories and social connections of youth. (December 2021) - Lima, Rebeca Fernandes Ferreira; Raffaelli, Marcela; Morais, Normanda Araujo de; Santana, Juliana Prates; Koller, Silvia H.
Abstract: Introduction: The heterogeneity of street-involved youth was examined using a person-centered approach. Youth were classified based on patterns of street involvement and the identified profiles compared to identify theoretically coherent and practically significant differences. Methods: Participants were 111 street-involved youth aged 9 to 18 ( M age = 14.15 years; 81.1% male, 91.1% non-white) from three Brazilian cities. Youth completed a life history interview and structured assessment. Latent class analysis was used to identify three profiles of youth based on reasons for going to the street and connections to major developmental contexts (street, family, institutions). Profile comparisons on psychosocial variables (e.g., age, life events) and adjustment indicators (e.g., drug use, life satisfaction) were conducted using multinomial logistic regression. Results: The largest profile (48.6%) included youth drawn to the street by drug use or trafficking, who had moderate connections to street and family. Another group (40.5%) went to the street to escape family dysfunction, and the street represented their primary developmental context. These groups differed on some psychosocial indicators but had similar patterns of adjustment. The third group of youth (10.8%) had families with a history of street involvement and maintained strong ties to all three developmental contexts. These youth had generally better adjustment than their peers (e.g., less drug use, higher life satisfaction) but had higher levels of sexual risk related to the overrepresentation of girls. Conclusions: Street involvement is a multidetermined phenomenon that may expose young people to distinct conditions of vulnerability. Findings have implications for research, practice, and policy.